Evolution of BIM: epistemology, genesis and division into periods - Borkowski, Andrzej Szymon (Journal of information technology in construction, 2023)
There is no consensus among BIM practitioners and theorists as to whether BIM is an evolution from CAD systems or a total revolution in construction. In the history of BIM, there have been a number of important, epoch-making events that have changed the direction of BIM. From the concept of BIM, to the technology used in construction, to the methodology, to the process, to the holistic idea of BIM, one can see the evolution of user approaches to its use. BIM has two dimensions: an information system and a philosophy. Thus, BIM is both a tool and a philosophy that brings about a revolution. Several decades of BIM development prompts reflection and the delineation of perhaps some stages of maturation. This paper presents a theory of cognition (epistemology), essential for understanding the history of BIM. The genesis of the separation of BIM from CAD makes it clear that specific factors influenced further developments. Thus, the aim of the study was to periodise BIM in view of various factors that may be relevant to researchers interested in BIM and companies using or implementing BIM. The literature survey maintained inclusivity to reflect both positive and critical aspects of BIM. The periodisation of the history of BIM was done due to 3 factors: idea, approach and organisational culture. The development of the BIM idea established the direction in which systems and software development was heading, the user approach forced interoperability and the organisational culture emphasised increasing efficiency. Working according to the openBIM approach or within an IPD framework is probably not the end of the anticipated level of BIM maturity. The division into periods will probably be the subject of much discussion, but will perhaps set the directions for the future.